Sikap konsumen terhadap produk kerupuk Dangke Melona dan tanpa merek di Kecamatan Cendana, Enrekang - Nur Aulia; St. Aisyah R; Sahlan; Sitti Khadijah Yahya Hiola (Universitas Sulawesi Barat, 2021)
The purpose of this study was to determine the consumer attitudes towards the product attributes of dangke crackers in Cendana District, Enrekang. The sampling technique used an accidental sampling of 50 consumers. This study uses primary and secondary data. The data were collected using observation, documentation, and interviews. The data analysis in this study was the Fishbein Multi-attribute analysis. The results showed the total value of consumer attitudes (Ao) of the Melona brand and without the brand, respectively 68.38 and 65.03. The packaging was an excellent attribute of the Melona brand. Thus, overall consumers were more satisfied with the Melona brand of dangke cracker products than unbranded dangke cracker products.